Tetrasomy 18p: Report of cognitive and behavioral characteristics. (21st April 2015) - O'Donnell, Louise; Soileau, Bridgette T.; Sebold, Courtney; Gelfond, Jonathan; Hale, Daniel E.; Cody, Jannine D.
<x xml:space="preserve">Abstract</x> Our purpose was to describe intellectual and behavioral characteristics of persons with tetrasomy 18p. This is a more detailed investigation into the cognitive and behavioral characteristics of our previously reported tetrasomy 18p cohort of 43 plus six additional participants. We evaluated the intellectual functioning using standard measures of cognitive ability, measures of executive functioning, adaptive and maladaptive behaviors. Intellectual abilities ranged from mild impairment/borderline normal to severe/profound impairment calling into question the assumption that severe cognitive limitation is always a feature of tetrasomy 18p. For persons with tetrasomy 18p with mild cognitive deficits, the main barriers to successful functioning stems from limited social and metacognitive skill development and behavior regulation problems rather than being solely determined by cognitive deficits alone. © 2015 Wiley Periodicals, Inc.